2020
DOI: 10.2169/internalmedicine.4684-20
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Combined Degeneration of the Spinal Cord Caused by Autoimmune Gastritis

Abstract: A 68-year-old woman presented with a 2-year history of worsening unsteady gait. Her neurological examination revealed peripheral neuropathy with lower limb sensory dominance. T2-weighted imaging revealed a disorder of the posterior cervical cord. Blood test findings revealed vitamin B12 deficiency, and gastroscopy revealed typical findings of autoimmune gastritis. She received vitamin B12 supplementation, but some peripheral neuropathy symptoms persisted due to longstanding vitamin B12 deficiency. Asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In the present case, although the patient was deficient in both iron and vitamin B 12 , the microcytic hypochromic anemia pattern suggests that iron deficiency anemia was predominant. Vitamin B 12 deficiency should not be overlooked because of the assumption that microcytic hypochromic anemia is simply due to iron deficiency, as chronic vitamin B 12 deficiency can cause irreversible peripheral neuropathy ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, although the patient was deficient in both iron and vitamin B 12 , the microcytic hypochromic anemia pattern suggests that iron deficiency anemia was predominant. Vitamin B 12 deficiency should not be overlooked because of the assumption that microcytic hypochromic anemia is simply due to iron deficiency, as chronic vitamin B 12 deficiency can cause irreversible peripheral neuropathy ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neumann et al ( 8 ) reported that SCD with malignant anemia was common among elderly patients. Several cases of SCD combined with autoimmune diseases, including rheumatoid arthritis ( 9 ), autoimmune gastritis ( 10 ), and ulcerative colitis ( 11 ), have been reported. The findings in our cases suggested that SCD-associated malignant anemia can only manifest as atypical gastrointestinal reactions or no reaction.…”
Section: Discussionmentioning
confidence: 99%
“…22 Oftedal et al found out heterozygous dominantnegative mutations in the AIRE gene. 23 Genetic studies in the index case revealed single copy (heterogenous) mutations of the AIRE gene in exon location 7 (NM_000383.3 c.841G>A chr21:45709913 p.Ala281Thr), with dominant inheritance. Moreover, researchers find that monogenetic mutations causing autoimmunity are less identified than they exist in reality, and also that the penetrance of the disease is variable (30-40%), rarely reaching hundred percent even among monozygotic twins.…”
Section: Case Reportmentioning
confidence: 99%